Luo music - Rycroft, David K. (International Library of African Music, 1975)
Rev. Dr. A.M. Jones and Prof. A.N. Tucker, together with Mr. Olum Oludhe, of the School of Oriental and African Studies, Malet Street, London WC1E 7HP, completed a few years ago a study entitled Woman the home (Dhako e pacho), an ethnomusical study of marriage rites among the Luo of Kenya. As they have not yet succeeded in finding a publisher, the authors would like to let scholars know that they have deposited two copies of the book, one in the Library of the School of Oriental and African Studies, and one in the Library of the University of Nairobi, P.O. Box 30197, Nairobi, in order that the work may be of use in the meantime.
Keywords: African Music